In Defense of Technical Analysis - TREYNOR, JACK L.; FERGUSON, ROBERT (Journal of Finance, 1985)
ABSTRACT Many investors occasionally receive what they believe to be nonpublic information about a security. Others feel that by applying superior analytical skills to public information, they are able to arrive at valuable insights that are not generally appreciated. In either case, there is a substantial opportunity for profit if the investor is correct. The investor must be correct on two counts. First, the estimate of the worth of the information must be reasonably accurate in terms of its impact on the price of the stock, and second, the investor must make a realistic assessment of the likelihood that the market already has received the information or insight in question. This paper is concerned only with the latter problem. The probability distribution of the date on which the market receives information already in the hands of the investor is calculated for a simple model of information propagation. It is then shown how this probability distribution can be brought to bear on the management of a portfolio.